Effects of hormonal contraceptives on physical performance and body composition - Myllyaho, Moona (2016)
The purpose of the present study was to examine the effects of hormonal contraceptive use on neuromuscular, cardiorespiratory and body composition adaptations following combined strength and endurance training period. Methods. Nineteen recreationally active women; 11 who had at least one year of hormonal contraceptive use (age 294 yr; BMI 212 kg/m2; VO2max 444 ml/kg/min) and 8 who had never used hormonal contraceptives (age 315 yr; BMI 222 kg/m2; VO2max 414 ml/kg/min) participated in the present study of combined strength and endurance training for 10 weeks. Training consisted of two maximal and explosive strength training sessions, and two high-intensity interval training sessions per week. Serum basal hormone levels, maximal bilateral isometric strength, maximal unilateral isometric knee extension and flexion, maximal bilateral dynamic leg press (1RM), counter movement jump (CMJ), upper body isometric strength, dynamic muscle endurance, a 3000 m running test and an incremental maximal running test were measured prior to the intervention and after the 10 weeks training period. Results. There were no statistically significant differences between groups’ improvements in any measured strength, endurance or body composition variables. The hormonal contraception users (HC) significantly improved their performance in maximal isometric leg press (14±15%, p<0.05), isometric knee flexion (11±14%, p<0.05), isometric bench press (9±7%, p<0.001), dynamic leg press (10±5% p<0.001), countermovement jump (6±7%, p<0.01), push-ups (14±16%, p<0.05) and sit-ups (22±25%, p<0.05). The non-users (NHC) had significant improvements in isometric leg press (6±6%, p<0.05), isometric knee extension (9±11%, p<0.05), dynamic leg press (7±4%, p<0.01), countermovement jump (11±6%, p<0.001), push-ups (20±17%, p<0.05) and sit-ups (13±11%, p<0.05). Maximal oxygen consumption (VO2max) remained unchanged in both groups. In the 3000 m time trial the HC group decreased their running time by 2±4% (p=0.162) and the NHC group by 3±2% (p<0.05). The improvement in time trial was significant only within the NHC group, however, there was not a significant difference between groups’ improvements (p=0.559). There were no statistically significant differences between groups’ improvements in body composition, however, a trend for greater increase in fat free mass was observed in NHC than in HC women (p=0.065). The HC group increased fat free mass by 11% (p<0.05) and the NHC group by 21% (p<0.001). Total fat was reduced in the HC group by 510% (p=0.158) and in the NHC group by 56% (p<0.05). Summary and conclusions. High-intensity combined strength and endurance training resulted in significant improvements in neuromuscular performance and fat free mass in both groups. In addition, there were significant improvements in 3000 m running performance and decreases in total body fat within the NHC group. These findings suggest that combined strength and endurance training is a useful method for improving physical fitness and health in recreationally active women, and hormonal contraception use does not appear to impair the physical performance or body composition.